La comprensión lectora y su relación con el rendimiento académico en el área de inglés, en alumnos del 5to grado de educación secundaria de la l.E. "Cleofe Arévalo del Aguila" del distrito de la Banda de Shilcayo en el año 2009 - Gutierrez Vargas, Gavy Marilin (2010)
In the learning process, to understand what it is read turns out to be fundamental, because the person tends to learn, in the most cases, through reading; therefore, the conduction of the teaching learning process should give him/her suitable capacities to understand a written text. The reading comprehension, however, is a latent problem since the students do not know how to understand with a minimum of fluency what they read. The present investigation entitled: The reading comprehension and its relationship with the academic performance in the area of foreign language, on students of the 5th year of secondary education in the School "Cleofe Arevalo Del Aguila" in the District of The Banda of Shilcayo, in the year 2009; it was guided that direct relation exists between the reading comprehension and academic performance in the area of foreign language on students of the 5th year of secondary education in the School "Cleofe Arevalo Del Aguila" in the District of The Banda of Shilcayo, in the year 2009. Field information was gathered, working with 75 students, by the application of an objective test of reading comprehension; and an analysis record to collect the information of the academic performance. The data were processes by frequencies distribution, arithmetic mean, variability measures and the Pearson's correlation coefficient. According to the Pearson's correlation coefficient (0,63), it was checked than direct relation exists between the reading comprehension and academic performance in the area of foreign language on students of the 5th year of secondary education in the School "Cleofe Arevalo Del Aguila" in the District of The Banda of Shilcayo, in the year 2009.